2000
DOI: 10.1021/la9913295
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Liquid/Liquid Interface in a Phase-Transfer Catalytic Reaction As Investigated by in Situ Measurements Using the Quasi-Elastic Laser Scattering Method

Abstract: The relationship between the concentration of a phase-transfer catalyst, tetrabutylammonium bromide (TBAB), and the rate of its cyclic reaction was investigated using the quasi-elastic laser scattering (QELS) method. TBAB forms an ion pair (TBA + C6H5O -) with sodium phenoxide (C6H5ONa) at the interface. This ion pair moves from the interface to the organic phase where it reacts with diphenylphosphoryl chloride and produces triphenyl phosphate. During this reaction, tetrabutylammonium chloride, which is genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…All chemical shift values (δ) were reported in parts per million (ppm), using the residual solvent signal of 7.67,7.50) as a reference. A series of NB-d5 solutions which contain target anions (HPO4 2-or SO4 2-, as a TBA + salt) and ionophore 1 was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…All chemical shift values (δ) were reported in parts per million (ppm), using the residual solvent signal of 7.67,7.50) as a reference. A series of NB-d5 solutions which contain target anions (HPO4 2-or SO4 2-, as a TBA + salt) and ionophore 1 was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] We fabricated a conventional laser heterodyne QELS measurement system using a diffraction grating as a local oscillator, and have reported on the dynamics of the mass transfer of surfactants at a liquid/liquid interface. [9][10][11][12][13] Furthermore, we devised a new principle of the QELS method using a monoluminous flux detection technique in a beam divergence, and have achieved 50 -100 times higher S/N ratios than the conventional heterodyne system. 14 Although the S/N ratio was substantially improved by a new technique, averaging of 20 -100 power spectra was necessary to estimate the capillary wave frequency.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Spontaneous oscillations by alcohol transfer through water/alkane interface 4,5 and at water/nitrobenzene interfaces have much in common. [6][7][8] Sha et al have reported that those spontaneous oscillation stably continued for 120 h and that the period was controllable by the interface area.…”
mentioning
confidence: 99%